The Correlation Between Mitigation and Community Preparedness in Facing Volcanic Eruption - Nirmalasari, Novita; Kurnia Katammi, Khoiriah (Journal for Quality in Public Health, 2025)
Turgo area is a disaster-prone area of Mount Merapi activity, and it is at high risk of being affected by Mount Merapi activity. Mitigation carried out by the community greatly influences community preparedness in facing disasters. This study aims to determine the correlation between mitigation and the level of community preparedness in facing the volcanic eruption of Mount Merapi in the Turgo area. This study is a descriptive correlative design using a cross-sectional approach. The study's respondents were 131 respondents selected using stratified random sampling techniques. Data was collected through valid and reliable disaster mitigation and disaster preparedness questionnaires. Data analysis was conducted using the Chi-Square test to determine the relationship between mitigation and preparedness variables. The study results showed that the level of community mitigation was mainly in the high category (96.9%), and the level of preparedness was primarily in the good category (93.9%). The analysis results using the Chi-Square test demonstrate no significant correlation between mitigation and preparedness in facing volcanic eruption (p>0.05; r=2,569). This means that there is no statistically significant relationship between mitigation and preparedness. However, there is an optimistic tendency that better mitigation is followed by higher preparedness. Communities with high mitigation tend to be well prepared. This study recommends a more comprehensive approach, including education, disaster simulations, and cross-sector collaboration to improve community preparedness.